Analysis of the Relationship Between E-Commerce Business and Technology-Based Accounting Information Systems with Company Audit Needs - Darmiono, Darmiono; Pratiwi, Rina (West Science Information System and Technology, 2024)
This study explores the relationship between E-commerce business operations, Technology-Based Accounting Information Systems (AIS) adoption, and corporate audit needs through a quantitative analysis approach. Drawing on data collected from 234 participants representing E-commerce firms and audit professionals, the study employs Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to analyze the relationships among key variables. The findings reveal significant positive associations between E-commerce characteristics and Technology-Based AIS adoption, as well as between Technology-Based AIS adoption and corporate audit needs. Furthermore, mediation analysis demonstrates that Technology-Based AIS adoption partially mediates the relationship between E-commerce characteristics and corporate audit needs. Additionally, moderation analysis indicates that firm size and industry type moderate these relationships, with larger firms and those in technology-intensive industries exhibiting stronger associations. These findings underscore the importance of technological innovation and organizational context in shaping audit readiness and effectiveness within E-commerce environments.